Manuel Castells. La Galaxia Internet. Plaza & Janés Editores, Madrid, 2001, 317 páginas. - Coppolecchio, Leandro G. (2002)
Fil: Coppolecchio, Leandro Gastón. Universidad Nacional de La Matanza; Argentina.